Two new species of Indonemoura (Plecoptera, Nemouridae) from Yunnan Province, China - Bai, Xue; Shen, Dan; Qian, Yu-Han (European Journal of Taxonomy, 2022)
Two new species of the family Nemouridae of the genus Indonemoura Baumann, 1975, Indonemoura yingjiangensis Bai & Qian sp. nov. and Indonemoura longihamata Bai & Qian sp. nov. are described from Yunnan Province, southwest of China. The morphological characteristics of the two new species are compared to related taxa.